Balinese Language and Local Identity in a Multicultural Context; Issues, Challenges, and Preservation Efforts: Bahasa dan Identitas Lokal Bali dalam Konteks Multikultural; Isu, Tantangan, dan Upaya Pelestariannya - Komang Puteri Yadnya Diari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
This research aims to present the issues, challenges and opportunities of Balinese regional languages ​​in the context of multicultural society and culture. In the current context, the Balinese language is experiencing a decline in interest and use in daily life which is being eroded by the use of Indonesian and English by the people. The great influence of multiculturalism is detected in this context. This is proven by the proliferation of international standard Kindergarten, Elementary, Middle and High Schools, where these schools present and promise English as the language of instruction. The narrative literature review method is used as empirical data to support arguments. Some of the issues facing the Balinese language currently and in the future include the code mixing habits of parents in Bali, the proliferation of international schools, and the position of the Balinese language in the Indonesian curriculum. These issues refer to several challenges faced by the existence of the Balinese language, namely the shift in the identity of the younger generation, changes in the educational curriculum, and the shift in the function of regional languages. Several efforts have been made by various parties in order to preserve the Balinese language in the context of a multicultural society. Steps that should be taken as preservation tips in the future are packaging the language with local culture, stabilizing diglossia, using Balinese as an introductory subject, training and community development, as well as linguistic research for documentation. With this research, it is hoped that the Balinese people will pay more attention to and preserve the Balinese language. Research related to Balinese is still limited. It is hoped that this paper will be able to contribute to literature studies for parties interested in researching the Balinese language further.